Analisis Bahan Bakar Campuran Methanol dengan Minyak Jarak terhadap Performa Engine 0S 4.6LA Pesawat Terbang Unmanned Aerial Vehicle (UAV) - Sotya Anggroro (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2021)
Technological progress is evidenced by the creation of sophisticated equipment made to simplify human life. One of the advanced equipment continuously developed is an uncrewed aircraft called the Unmanned Aerial Vehicle (UAV). This study used an Unmanned Aerial Vehicle (UAV) Super Heavy aircraft with a two-stroke engine type OS 4.6 LA where the two-stroke engine requires fuel which can also lubricate the piston while operating. The purpose of this research is to make an alternative fuel with a mixture of methanol and castor oil where castor oil has flammable properties like fuel in general but can provide better lubrication. In this research, an analysis of the mixture of methanol and castor oil will be carried out on engine performance and fuel consumption of an Unmanned Aerial Vehicle (UAV) aircraft with an engine type OS 4.6 LA. This research aims to compare methanol and castor oil with a ratio of 3:1 and 4:1, then test engine performance and fuel consumption. The results confirm that a 4: 1 mixture is the best performer with a stationary rotation of 4184 rpm, an idle rotation of 7344 rpm, and an acceleration rotation or the highest rotation of 12649 rpm. Then the fuel efficiency in the idle position with a flight time of 9.00 minutes consumes 100 ml of fuel, or in other words, the fuel consumption is 11.11 ml/minute.